Cancer reversion with oocyte extracts is mediated by cell cycle arrest and induction of tumour dormancy - Saad, Norazalina; Alberio, Ramiro; Johnson, Andrew D.; Emes, Richard D.; Giles, Tom C.; Clarke, Philip; Grabowska, Anna M.; Allegrucci, Cinzia (Impact Journals, 2018)
Inducing stable control of tumour growth by tumour reversion is an alternative approach to cancer treatment when eradication of the disease cannot be achieved. The process requires re-establishment of normal control mechanisms that are lost in cancer cells so that abnormal proliferation can be halted. Embryonic environments can reset cellular programmes and we previously showed that axolotl oocyte extracts can reprogram breast cancer cells and reverse their tumorigenicity. In this study, we analysed the gene expression profiles of oocyte extract-treated tumour xenografts to show that tumour reprogramming involves cell cycle arrest and acquisition of a quiescent state. Tumour dormancy is associated with increased P27 expression, restoration of RB function and downregulation of mitogen-activated signalling pathways. We also show that the quiescent state is associated with increased levels of H4K20me3 and decreased H4K20me1, an epigenetic profile leading to chromatin compaction. The epigenetic reprogramming induced by oocyte extracts is required for RB hypophosphorylation and induction of P27 expression, both occurring during exposure to the extracts and stably maintained in reprogrammed tumour xenografts. Therefore, this study demonstrates the value of oocyte molecules for inducing tumour reversion and for the development of new chemoquiescence-based therapies.